2018
DOI: 10.1002/stc.2169
|View full text |Cite
|
Sign up to set email alerts
|

Design of structure with inerter system based on stochastic response mitigation ratio

Abstract: Summary An easy‐to‐use method for a practical design of single‐degree‐of‐freedom (SDOF) structures with inerter systems was developed. The method adopts the stochastic vibration response mitigation ratio as the design index, and expressions of the closed‐form stochastic response are used to evaluate the structural response and optimize the design parameters. Three basic types of inerter systems with tuning and damping magnification mechanisms were considered in this study. The closed‐form stochastic responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 51 publications
(86 reference statements)
1
75
0
1
Order By: Relevance
“…The ideal mechanical layouts of two representative series–parallel inerter systems, TID and TVMD, are shown in Figure , where m in , c d , and k d are the inertance of the inerter element, the damping coefficient of the EDE, and the stiffness of the spring element, respectively. For these two typical types of inerter systems, the inerter and the spring are connected in series in both systems, whereas the configurations of the EDEs are different; EDEs are mounted in parallel with the spring and inerter in the TID and TVMD, respectively.…”
Section: Damping Enhancement Equation and Theoretical Basismentioning
confidence: 99%
See 3 more Smart Citations
“…The ideal mechanical layouts of two representative series–parallel inerter systems, TID and TVMD, are shown in Figure , where m in , c d , and k d are the inertance of the inerter element, the damping coefficient of the EDE, and the stiffness of the spring element, respectively. For these two typical types of inerter systems, the inerter and the spring are connected in series in both systems, whereas the configurations of the EDEs are different; EDEs are mounted in parallel with the spring and inerter in the TID and TVMD, respectively.…”
Section: Damping Enhancement Equation and Theoretical Basismentioning
confidence: 99%
“…Mechanical models of classic series–parallel layout inerter systems . EDE, energy dissipation element; SPIS‐I, series–parallel layout I inerter system; SPIS‐II, series–parallel layout II inerter system; TID, tuned inerter damper; TVMD, tuned viscous mass damper…”
Section: Damping Enhancement Equation and Theoretical Basismentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al defined four performance indices to evaluate the isolation performance of the inerter‐based vibration isolator and showed that it can achieve a better isolation performance compared with the linear spring–damper vibration isolator. The inerter has also been applied in other structures due to its mechanical property, including vehicle suspension, motorcycle steering system, train suspension, building vibration control system, landing gear, dynamic vibration absorber, and tuned mass damper . The researches show that when the inerter is used, these mechanical systems can achieve a superior performance.…”
Section: Introductionmentioning
confidence: 99%